Electroactive and Electroactive Chemical Polymers and Their Applications: Review - Nagham Mahmood Aljamali; Jihan Razzaq Moslim, Fatimah A .Wannas (Journal of Electronic Design Engineering, 2021)
From the present review, we have collected extensive studies of active and electrically active electronic polymers and their applications, which have shown a change in size or shape when stimulated by an electric field. One of the distinguishing characteristics of electroactive polymers is that no matter how much crushing force they are subjected to, they will maintain strong forces and last for long periods. Older mechanical actuators are made of piezoelectric ceramic materials. It was demonstrated in the late 1990s that some electroactive polymers can withstand stresses up to (380%), which is much greater than that of any ceramic actuator. Usually, electrically active conductive polymers are intrinsically conductive or at least semiconductive. They sometimes exhibit mechanical properties similar to those of conventional organic polymers. Both organic synthesis and advanced dispersion techniques can be used to tune the electrical properties of conductive polymers, in contrast to typical inorganic conductors. The well-studied types of conductive polymers include polyacetylene, polypyrrole, polyaniline, and their copolymers. Polyphenylene and its derivatives are used in electrically semiconducting polymers. It is also considered poly3-alkyl thiophene, an ideal material for use in solar cells and transistors.